2011
DOI: 10.1021/ic201427w
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization of the Lanthanide-Ion-Driven Magnetic Properties in a Series of 4f–5d Cyano-Bridged Chains

Abstract: Magnetic properties of new d-f cyanido-bridged 1D assemblies [RE(pzam)(3)(H(2)O)W(CN)(8)]·H(2)O (RE(III) = Gd, 1, Tb, 2, Dy, 3; pzam = pyrazine-2-carboxamide) were studied by temperature- and field-dependent magnetization measurements. No evidence for 3D interchain magnetic ordering is found above 2 K. Multiconfiguration ab initio calculations and subsequent modeling afforded simulation of the weak zero-field splitting effect in 1 and discussion of magnetic anisotropy in the f units of compounds 2 and 3. A sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…While working in the vicinity of our LFDFT developed approach, this methodological update will also help for the reliable determination of the magnetic properties of lanthanide or transition metal complexes being currently popular in theoretical research. [58][59][60][61][62][63][64][65] The formulation of the ligand field interaction, which takes into account the presence of the ligands in the coordination sphere of the lanthanide, is also the subject of intense work. 32,44 Here, the ligand field potential includes two distinct interactions the perturbation of the 4f and 5d orbitals of the lanthanide, respectively, leading to ligand field matrix of 12 by 12 elements.…”
Section: Resultsmentioning
confidence: 99%
“…While working in the vicinity of our LFDFT developed approach, this methodological update will also help for the reliable determination of the magnetic properties of lanthanide or transition metal complexes being currently popular in theoretical research. [58][59][60][61][62][63][64][65] The formulation of the ligand field interaction, which takes into account the presence of the ligands in the coordination sphere of the lanthanide, is also the subject of intense work. 32,44 Here, the ligand field potential includes two distinct interactions the perturbation of the 4f and 5d orbitals of the lanthanide, respectively, leading to ligand field matrix of 12 by 12 elements.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] We mention also the situation of non-aufbau occupation [9][10][11][12] of the 4f orbitals inasmuch as convergence problems may frequently occur in the self-consistent field (SCF). The calculation of the f-d transitions in lanthanide phosphors is addressed with respect to the ligand field theory 13,14 but not restricted to its classical empirical frame.…”
Section: +mentioning
confidence: 99%
“…Previously, we reported the synthesis and magnetothermal studies of heterometallic rareearth (RE) -based cyanido-bridged 1D complexes, namely, [RE(pzam) 3 (H 2 O)Mo(CN) 8 ]·H 2 O (RE = Nd, Sm, Gd, Tb, and Er, pzam = pyrazine-2-carboxamide), whose magnetic properties are mainly determined by the particular RE ion involved. [7][8][9][10][11] We found that the Nd(III) and Mo(V) ions are coupled ferromagnetically into magnetic chains by an XY -type (planar) interaction. 10 The interaction between Tb(III) and Mo(V) is likewise ferromagnetic, but with a strong Isingtype anisotropy.…”
Section: Introductionmentioning
confidence: 91%